Risk Screening for Hereditary Cancer During Obstetrical Care: Barriers to Testing and Health Disparities [27M]. (May 2018) - Lua, Lannah L.; Jackson, David; Foggia, Megan; Rosenbaum, Amy
Abstract : INTRODUCTION: Hereditary cancer screening performed during routine prenatal care may identify mutation positive women years before disease progression. Our primary goal was to quantify the acceptance and efficacy of a focused cancer screening program initiated during pregnancy intake. Our secondary goal was to determine if at-risk patients who accept gene testing have barriers to obtaining mutation screening. METHODS: In this prospective study, a self-administered cancer history questionnaire was obtained at the first prenatal visit in three urban clinics from February 2015 to April 2016. National Comprehensive Cancer Network criteria identified patients for additional information regarding BRCA or Lynch mutation testing. Patients at increased risk received immediate physician counseling and were also offered genetic counseling. Desire for mutation screening and barriers to completing genetic testing were quantified. RESULTS: There were 942 patients screened. The at-risk prevalence was 11.4% (n=107/942). Acceptance for gene testing was 33.6% (n=36/107). Mean age of at-risk/criteria-positive patients was 27.9 +/- 6.8 years (range 15-43). Among at-risk patients, 33.6% were Non-Hispanic White, 29.0% were Hispanic, and 27.1% were African American. Financial barriers, insurance denials, and poor access to genetic counselors limited testing to less than 5% of those who requested it. CONCLUSION: Obstetrical consultation is a potential "teachable moment" in hereditary cancer screening. A health disparity exists when patients cannot obtain the desired testing due to financial limitations. Future studies should be structured to remove financial barriers to genetic counseling and mutation testing. If successful, the paradigm of screening during obstetrical care could potentially identify at-risk women decades before disease development.